Targum Chronicles and Its Place Among the Late Targums - Gottlieb, Leoor (Supplement to Aramaic Studies, 2020)
Targum Chronicles and Its Place Among the Late Targums heralds a paradigm shift in the understanding of many of the Jewish-Aramaic translations of individual biblical books and their origins. Leeor Gottlieb provides the most extensive study of Targum Chronicles to date, leading to conclusions that challenge long-accepted truisms with regard to the origin of Targums. This book's trail of evidence convincingly points to the composition of Targums in a time and place that was heretofore not expected to be the provenance of these Aramaic gems of biblical interpretation. This study also offers detailed comparisons to other Targums and fascinating new explanations for dozens of aggadic expansions in Targum Chronicles, tying them to their rabbinic sources.